Acitretin in dermatology - Rashmi Sarkar; Amit Kumar Meena (Apollo Medicine, 2023)
Introduction/Background: Acitretin is a second-generation systemic retinoid. Its clinical applications are virtually exclusively limited to dermatology. It has anti-inflammatory, antiproliferative, and antikeratinizing effects. However, there is a lack of articles summarizing the relevant literature in a systemic way. Methods: A PubMed search was performed using keywords such as “retinoids,” “acitretin,” “etretinate,” and “retinoid embryopathy” to identify relevant original articles, case series, and case reports. Results: The most commonly used application of acitretin, a second-generation systemic retinoid is in the treatment of psoriasis. It has been used in various other dermatological disorders (keratoderma, ichthyosis, pityriasis rubra pilaris, and lichen planus) as a stand-alone therapy or may be combined with other topical and systemic agents. As the drug is not an immunosuppressive agent, hence can be given safely to patients suffering from human immunodeficiency virus and taking highly active antiretroviral therapy. The drug can be given safely in the pediatric as well as the adult population. Although adverse effects are common usually minor and self-limiting and can be managed easily without stopping the drug. The main side effects of the drug include teratogenicity, hepatotoxicity, and hyperlipidemia which should be monitored regularly. It should be avoided or used cautiously in patients taking methotrexate, cyclosporine, and corticosteroids. Conclusions: This article has discussed various uses of acitretin in dermatology, its side effect profile, indication, contraindication, and drug interactions. The drug can be administered safely and successfully with the right patient selection, progressive dose increase, careful monitoring, and appropriate patient counseling.